Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

9x - 3 = 7 (x + 3) + 2n

answer and ur marked brainly master​


Sagot :

Hey there!

9x - 3 = 7(x + 3) + 2n

➡️ 9x - 3 = 7(x) + 7(3) + 2n

➡️ 9x - 3 = 7x + 21 + 2n

ADD -7x to BOTH SIDES

2n + 7x + 21 + (-7x) = 9x - 3 + (-7x)

SIMPLIFY IT!

2n + 21 = 2x - 3

ADD -21 to BOTH SIDES

2n + 21 + (-21) = 2x - 3 + (-21)

SIMPLIFY THIS AS WELL!

2n = 2x - 24

DIVIDE 2 to BOTH SIDES

2n/2 = (2x - 24)/2

FINALLY SIMPLIFY THIS LAST STEP!

n = x - 12

Answer: n = x - 12

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.